Analisis Pemberdayaan Ekonomi Mustahik Melalui Pendayagunaan Zakat Pada Program Kampung Zakat di Tulungagung - Bariroh, Muflihatul; Amiliskina (Fakultas Syariah IAIN Kediri, 2024)
This research is motivated by the emergence of a zakat management model with the launch of the zakat village initiated by the Ministry of Religion with the National Amil Zakat Agency which is intended to reduce poverty and seek the welfare of mustahik zakat recipients. These efforts are made to encourage the economy of the people which aims to alleviate poverty in underdeveloped outer areas including in the village of Besole Tulungagung. This research aims to describe and analyze the various programs contained in the zakat village through the perspective of empowerment and utilization of zakat so as to obtain comprehensive information and explanations related to the successful implementation of the zakat village program in Tulungagung. This research is a qualitative type with a case study approach in the field. Data sources were obtained through direct observation in Besole village, interviews with related parties and documentation. The result of the research shows that kampung zakat is a zakat management development program, which is not only consumptive but also productive. Some programs in the zakat village as an effort to empower the community are well implemented and have a very positive impact on the economy of mustahik in Besole village even though it has not run optimally. The program that can be said to be successful according to the author's opinion is the goat livestock assistance program, as evidenced by the growing number of recipients and the number of goats.